Vegetation Dynamics and Hydro-Climatic Changes during the Middle Holocene from the Central Himalaya, India - Mohammad Firoze Quamar; Anoop K. Singh; Lalit M. Joshi; Bahadur S. Kotlia; Dhruv Sen Singh; Corina Anca Simion; Tiberiu Sava; Nagendra Prasad (Quaternary, 2023)
Understanding the spatiotemporal monsoonal variability during the Holocene helps in understanding the rise and fall of many civilizations. In this study, a 2.65 m high palaeo lake sedimentary profile from the Kumaun Lesser Himalaya, Uttarakhand State, India was pollen analysed to reconstruct the variability in the monsoonal precipitation during the Middle Holocene. The study revealed that between ~7522 and 7216 cal yr BP, conifers dominated mixed broad-leaved forests occurred around the landscape of the study area, indicating a less cold and dry climate with decreased monsoon precipitation. Broad-leaved taxa during this phase show increased values considerably, indicating amelioration in climatic condition, which could be, in global perspective, broadly falling within the time-interval of the Holocene Climate Optimum (HCO; 7000–4000 BP). Between ~7216 and 6526 cal yr BP, dense conifers-dominated mixed broad-leaved forests transformed the conifers-dominated broad-leaved forests around the study area under a cold and drier climate with further reduction in monsoon precipitation. Subsequently, between ~6526 and 5987 cal yr BP, conifers-dominated broad-leaved forests continued to grow, but with lesser frequencies, around the study area under a comparatively less cold and dry climate with reduced monsoon precipitation. Finally, between ~5987 and 5817 cal yr BP, the frequencies of conifers-dominated broad-leaved forests further decreased around the landscape of the study area under a comparatively lesser cold and dry climate, probably indicating decreased monsoonal precipitation. Hence, the present study mainly showed the dominance of conifers forests around the study area between ~7522 and 7216 cal yr BP, ~7216 and 6526 cal yr BP, ~6526 and 5987 cal yr BP and between ~5987 and 5817 cal yr BP; however, broad-leaved forests also demonstrated increasing tendency between ~7522 and 7216 cal yr BP in the milieu of cold and dry climates. Moreover, the study also revealed that a lake was formed around 7522 cal yr BP along the Kulur River, a tributary of Saryu River around the study area and existed until 5817 cal yr BP.